IMPLEMENTASI 3D VIRTUAL TOUR DI SMKN 1 GLAGAH BANYUWANGI - Prasetyo, Junaedi Adi; Ayatullah, Muhammad Dimyati; Putra, Adetya Prananda (Jurnal Terapan Abdimas, 2020)
Abstract. This community service aims to create an online information media about the web-based school environment at SMK 1 Glagah, located on Jl. Kuntulan No. 1 Banyuwangi, Banjarsari, Glagah District, Banyuwangi by utilizing virtual reality technology. This web-based system is in the form of a Virtual tour with several locations in SMKN 1 Glagah which is a combination of several 360 ° horizontal panoramic images. Implementation of community service is carried out by conducting field surveys, determining the location of points, taking panoramic images in each location, merging images as well as making a virtual tour, virtual tour trials on localhost & evaluation and continued with hosting & website publication. The web that can be accessed in https://jelajah.smkn1glagah.sch.id has 21 location points starting from the main page in front of the school to the location of the workshop department at SMKN 1 Glagah. The benefits of a virtual web tour are as a medium for introducing an online school environment to the public, especially for the prospective new students.Abstrak. Kegiatan pengabdian ini bertujuan untuk membuat sebuah media informasi daring mengenai lingkungan sekolah berbasis web di SMKN 1 Glagah yang berlokasi di Jl. Kuntulan No. 1 Banyuwangi, Banjarsari, Kecamatan Glagah, Kabupaten Banyuwangi, Provinsi Jawa Timur dengan memanfaatkan teknologi virtual reality. Sistem berbasis web ini berupa Virtual tour dengan beberapa titik lokasi didalam SMKN 1 Glagah yang merupakan gabungan dari beberapa gambar panorama 360° horizontal. Pelaksanaan pengabdian kepada masyarakat ini dilakukan dengan melakukan survei lapangan, penentuan titik lokasi, pengambilan gambar panorama disetiap lokasi, penggabungan gambar sekaligus pembuatan web virtual tour, percobaan virtual tour di localhost & evaluasi serta dilanjutkan dengan hosting & publikasi website. Web dengan domain jelajah.smkn1glagah.sch.id ini memiliki 21 titik lokasi mulai dari halaman utama yang berada di depan sekolah hingga lokasi bengkel jurusan di SMKN 1 Glagah. Manfaat Web virtual tour adalah sebagai media pengenalan lingkungan sekolah secara daring bagi masyarakat umum terutama calon peserta didik baru.